Influence of Cr on the quaternary FeTaTiW medium entropy alloy - R. Martins; B. Monteiro; A. P. Gonçalves; J. B. Correia; A. Galatanu; E. Alves; E. Tejado; J. Y. Pastor; M. Dias (Journal of Materials Science: Materials in Engineering)
Abstract The search for advanced materials has been growing, and high entropy alloys (HEAs) are emerging as promising candidates for application in the fusion domain. This work investigates the effect of Cr on the FeTaTiW medium entropy alloy to form (CrFeTaTi)70W30 high entropy alloy, comparing the experimental production and characterization with the simulation (molecular dynamics and hybrid molecular dynamics-Monte Carlo) of the phases formed. The alloys were produced by mechanical alloying and sintered by spark plasma sintering. Both simulations have shown that a body-centered cubic structure is formed for both compositions. Monte Carlo simulation provides a more precise prediction of microstructural formation and element segregation. Microstructural examination of the consolidated material revealed the presence of a W-rich phase and a Ti–rich phase, consistent with the phase separation observed in the MC simulations. Moreover, X-ray diffraction analysis of the milled powder for FeTaTiW and (CrFeTaTi)70W30 confirmed the formation of a bcc (body-centered cubic)-type structure with a low fraction of intermetallic phases. Mechanical testing showed ductile behavior at 1000 °C where (CrFeTaTi)70W30 showed a stress magnitude almost double that of FeTaTiW. Additionally, the thermal diffusivity between 20 and 1000 °C of both alloys increases as the temperature rises. (CrFeTaTi)70W30 exhibits an increase from 3 to 5 mm2/s, while FeTaTiW increases from 4 to 9 mm2/s. Still, both system’s thermal diffusivity values are lower than those of CuCrZr and pure tungsten. Despite this, the study underscores the promising attributes of HEAs and highlights areas for further optimization to enhance its suitability for extreme conditions.